Complex I mutations synergize to worsen the phenotypic expression of Leber's hereditary optic neuropathy - Ji, Yanchun; Zhang, Juanjuan; Lu, Yuanyuan; Yi, Qiuzi; Chen, Mengquan; Xie, Shipeng; Mao, Xiaoting; Xiao, Yun; Meng, Feilong; Zhang, Minglian; Yang, Rulai; Guan, Min-Xin (The Journal of biological chemistry, 2020)
Leber's hereditary optic neuropathy (LHON) is a maternal inheritance of eye disease because of the mitochondrial DNA (mtDNA) mutations. We previously discovered a 3866T>C mutation within the gene for the ND1 subunit of complex I as possibly amplifying disease progression for patients bearing the disease-causing 11778G>A mutation within the gene for the ND4 subunit of complex I. However, whether and how the ND1 mutation exacerbates the ND4 mutation were unknown. In this report, we showed that four Chinese families bearing both m.3866T>C and m.11778G>A mutations exhibited higher penetrances of LHON than 6 Chinese pedigrees carrying only the m.3866T>C mutation or families harboring only the m.11778G>A mutation. The protein structure analysis revealed that the m.3866T>C (I187T) and m.11778G>A (R340H) mutations destabilized the specific interactions with other residues of ND1 and ND4, thereby altering the structure and function of complex I. Cellular data obtained using cybrids, constructed by transferring mitochondria from the Chinese families into mtDNA-less (ρ°) cells, demonstrated that the mutations perturbed the stability, assembly, and activity of complex I, leading to changes in mitochondrial ATP levels and membrane potential and increasing the production of reactive oxygen species. These mitochondrial dysfunctions promoted the apoptotic sensitivity of cells and decreased mitophagy. Cybrids bearing only the m.3866T>C mutation displayed mild mitochondrial dysfunctions, whereas those harboring both m.3866T>C and m.11778G>A mutations exhibited greater mitochondrial dysfunctions. These suggested that the m.3866T>C mutation acted in synergy with the m.11778G>A mutation, aggravating mitochondrial dysfunctions and contributing to higher penetrance of LHON in these families carrying both mtDNA mutations.